Designer's guide to Eurocode 1 : actions on bridges : EN 1991-2, EN 1991-1-1, -1-3 to -1-7 and EN 1990 annex A2 - Calgaro, J. A. (Designers' guides to the eurocodes., 2010)
The design process of a bridge includes several steps. One of the major steps is the determination of actions & combinations of actions. These actions are imposed loads due to traffic, climatic actions, actions due to water or soil subsidence, construction loads & accidental actions.